Analisis Penerapan Total Productive Maintenance (Tpm) Untuk Mendapatkan Nilai Overall Equipment Effectiveness (Oee) di PT. XYZ - Choerul Anam; Sukanta Sukanta (Peneliti.net, 2022)
The implementation of Total Productive Maintenance (TPM) is one of the goals to ensure all fixtures and production machines operate in the best condition so as to avoid damage so that they can prevent problems in the production process. The implementation of Total Productive Maintenance (TPM) carried out by the company, one of which is Planned Maintenance (PM) where the procedures for carrying out Planned Maintenance (PM) activities start from the Planned Maintenance Plan then the Planned Maintenance Work Instruction and are equipped with a Planned Maintenance Record. As an indicator is OEE (Overall Equipment Effectiveness) where at PT. XYZ in the three months starting from January to March 2022 where the achievements are in January by 91.09%, in February by 91.83% and in March by 93.53%, so that the average OEE achievement is 92, 15%. And these results exceed 1.15% of the target set by the company, which is 91.00%.